The Role of Social Power in Neural Responses to Others’ Pain - Ma, Xueling; Wu, Kai; Zhang, Entao (Frontiers in Psychology, 2019)
Recent evidence has demonstrated that empathic responses are modulated by social power. However, there is little consensus regarding how an observer’s social power can shape empathic responses. The present study used event-related potentials (ERPs) to explore the role of social power in empathic responses. Specifically, to induce the sense of power, we asked participants to recall a past situation in which they were in a position of power (high power prime) or a situation in which they were lacking power (low power prime). Afterward, we used event-related potentials (ERPs) to record the responses when participants were viewing pictures depicting other people in painful or non-painful situations. The results revealed that larger amplitudes in the earlier P2 and the later P3 components in response to painful stimuli than to non-painful stimuli. In addition, participants primed with high power only showed larger P1 amplitudes than participants primed with low power, however, the effect of power on P1 was weak. The present study extended previous studies by showing that social power tends to enhance the early sensory processing of both painful and non-painful stimuli, instead of directly decreasing the level of empathic responses to others’ pain.